Specification for tunnelling - British Tunnelling Society (BTS) (Emerald Publishing Limited, 2023)
The BTS Specification for Tunnelling has become the standard industry document for tunnelling contracts and forms the basis of tunnelling specifications for projects throughout the world. Since the publication of the third edition in 2010 the British tunnelling industry has completed several major projects both domestic and abroad. This updated fourth edition captures the many advances made in the field of tunnelling and the lessons learned on these projects through a comprehensive review of all content by subject matter experts. The importance of sustainability and the increased market share of low CO2e materials have been reflected by removal of prescriptive requirements and a strong emphasis on performance based specification. All references to codes, standards and other design documents have been comprehensively updated. Drafted by an expert editorial committee and supported by multiple rounds of industry wide peer reviews, the Specification for Tunnelling in its 4th edition will continue to be the de facto standard reference work for tunnelling in the UK and rest of the world.